Apolipoprotein E lipoprotein particles inhibit amyloid-β uptake through cell surface heparan sulphate proteoglycan. Issue 1 (December 2016) - Fu, Yuan; Zhao, Jing; Atagi, Yuka; Nielsen, Henrietta; Liu, Chia-Chen; Zheng, Honghua; Shinohara, Mitsuru; Kanekiyo, Takahisa; Bu, Guojun
Abstract Background The accumulation, aggregation and deposition of amyloid-β (Aβ) peptides in the brain are central to the pathogenesis of Alzheimer's disease (AD). Alzheimer's disease risk increases significantly in individuals carrying one or two copies ofAPOE ε4 allele compared to individuals with an ε3/ε3 genotype. Growing evidence has demonstrated that apolipoprotein E (apoE) strongly influences AD pathogenesis by controlling Aβ aggregation and metabolism. Heparan sulphate proteoglycans (HSPGs) are abundant cell surface molecules that bind to both apoE and Aβ. HSPGs have been associated with Aβ aggregation and deposition. Although several lines of research have shown that apoE influences Aβ clearance in the brain, it is not clear how apoE influences HSPG-mediated cellular uptake of Aβ. Results In this study, we show that apoE lipoprotein particles from conditioned media of immortalized astrocytes isolated from humanAPOE -targeted replacement (TR) mice significantly suppress cellular Aβ42 and Aβ40 uptake through cell surface HSPG. ApoE3 and apoE4 particles have similar binding affinity to heparin, while apoE4 particles are likely hypolipidated compared to apoE particles. We also found that the apoE particles antagonize Aβ binding to cell surface, and inhibited Aβ uptake in a concentration-dependent manner in Chinese hamster ovary (CHO) cells. While the effect was not apoE isoform-dependent, the suppressive effect of apoE particles on Aβ uptake was not observed in HSPG-deficient CHO cells. We further demonstrated that apoE particles reduced the internalization of Aβ in mouse primary neurons, an effect that is eliminated by the presence of heparin. Conclusions Taken together, our findings indicate that apoE particles irrespective of isoform inhibit HSPG-dependent cellular Aβ uptake. Modulating the ability of apoE particles to affect Aβ cellular uptake may hold promises for developing new strategies for AD therapy.